A Study for Enhancing the Spiritual Nursing Care Competence of Nursing Students - Choi , Ae-sook; Lee, Do-Young (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study is a descriptive comparative study to investigate the effects of nursing students' completion of the spiritual nursing curriculum on spirituality, spiritual well-being, and spiritual nursing care performance.Methods/Statistical analysis: The nursing students who completed the spiritual nursing curriculum earned one credit each with theory and practice for 15 weeks. The data analysis used SPSS version 23.0 by the collected questionnaire.Findings: As a result, the two groups have not shown a statistically significant difference in the spirituality and the spiritual well-being scores, but there were statistically significant differences in the score of spiritual nursing care performance. So it can be seen that performing spiritual nursing care is being possible only if the spiritual nursing curriculum and practice is existed in the college of the nursing curriculum.Improvements/Applications: It’s expected that the basic data will be utilized to continuously improve the nursing students' spiritual nursing care competence and to prepare for the nursing college curriculum through this study.